Exemplification and categorization the case of Japanese - Barotto, Alessandra (Trends in linguistics. Studies and monographs ;, 2021)
The book aims to examine the relationship between exemplification and categorization, using linguistic data from Japanese to better understand how people create and communicate conceptual categories in real-life situations (cf. the notion of ad hoc categories). In the book, exemplification is defined in functional terms as a process through which a speaker signals that a given entity should be construed as representative of a larger category of similar entities. The status of example can thus be encoded by means of dedicated analytical markers that overtly signal the exemplifying relation (e.g. for example), but also by making explicit reference to the larger category from which the examples have been selected. Through a case-study on four Japanese exemplifying markers (ya, nado, tari, toka), this book aims to understand (i) how examples are used and encoded by speakers to make reference to conceptual categories, (ii) what types of categories speakers can create and communicate by means of exemplification, (iii) how the relationship between exemplification and categorization can be used by speakers to achieve specific discourse effects, such as vagueness and politeness.